2022
DOI: 10.1007/1345_2022_173
|View full text |Cite
|
Sign up to set email alerts
|

On the Accuracy of Geoid Heights Derived from Discrete GNSS/Levelling Data Using Kriging Interpolation

Abstract: Local geoid models presenting higher resolution than global ones are generally derived by a combination of different datasets, integrating individual pure astrogeodetic, gravimetric and GNSS/levelling solutions. To define local geoid, different interpolators may be applied starting from dataset of geoid height values. It is well known that the accuracy of the resulting models depends not only by interpolation method, but also by points numerosity and distribution. This article aims to analyse the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Anyway, only the bias obtained for SD1, SD2 and SD3 (lowest sampling densities) were significantly different from zero (no bias), showing a low average positive bias that, in any case, was below 10 cm. This is likely due to the fact that UK needs high sampling densities to obtain more accurate results [77]. Note that UK is prone to overestimating the actual seabed depth, since it assumes that the mean depends on spatial location [66].…”
Section: Vertical Systematic Errormentioning
confidence: 99%
“…Anyway, only the bias obtained for SD1, SD2 and SD3 (lowest sampling densities) were significantly different from zero (no bias), showing a low average positive bias that, in any case, was below 10 cm. This is likely due to the fact that UK needs high sampling densities to obtain more accurate results [77]. Note that UK is prone to overestimating the actual seabed depth, since it assumes that the mean depends on spatial location [66].…”
Section: Vertical Systematic Errormentioning
confidence: 99%
“…The TG03 and EGM2008 models were found to be about 2 times less accurate than the precise local geoid models. Alcaras et al created a geoid model of the island of Corsica, France, which includes 81 rows and 40 columns, has a grid spacing of 1.5 in latitude and 2 in longitude, covering an area of about 24,767 km 2 [22]. It was found that ordinary kriging gives more accurate results than universal kriging, but the discrepancies between two models are minimal when there is high number of points.…”
Section: Fig 7 Construction Of the Map With Data From The Calculation...mentioning
confidence: 99%